Leadership of school principals and monitoring of students by their parents in Bamako - BAMBA , Amadou; DEMBELE , Kalifa; MAIGA , Abdoulaye; Soumaïla MOULAYE, Abdoulaye (International Journal of Scientific Research and Management (IJSRM), 2023)
The objective of this paper is to understand the link between the leadership of school principals and the monitoring of students by their parents. Indeed, the leadership of the principals should make it possible to bring the parents to take more interest in the follow-up of the pupils. A leadership test was thus administered to 6 directors (school principals) of private and public school groups from the Rive Droite Academy in Bamako; 480 students were quizzed about parental support and then an interview guide was sent to teachers, school principals and parents of students who are members of School Management Committees in the schools in the sample (CGS) to decide on the leadership of the directors and the follow-up of the pupils by their parents.The results of the school principal’s leadership test show that 4 out of 6 directors have a good overall leadership score. The score for task orientation is the highest, followed by the score for democratic and participatory leadership; that for orientation towards pupils' parents is lower among all directors. In addition, 62.5% of students who benefit from parental support come from schools run by directors who have a good leadership score. The results of the interviews show that the directors of public schools find that the follow-up of pupils by their parents is not linked to their leadership but rather to the level of poverty of the parents, which poses the problem of school follow-up for their children. However, the directors of private schools specify that they themselves must find channels of communication with parents in order to sensitize them to follow their children. For teachers, directors of successful schools in Mali have a high level of democratic leadership. Four representatives of the parents of pupils think that the principals of schools do not make enough efforts to push the parents to be firm with their children. The other two representatives find that school principals are discouraged by the marked indiscipline of children due to the fact that parents do nothing to educate their children and encourage them to take their studies seriously.